Knowledge and myths about eating disorders in a German adolescent sample: a preliminary investigation - Feldhege, Johannes; Bilić, Sally Sophie; Ali, Kathina; Fassnacht, Daniel B.; Moessner, Markus; Farrer, Louise M.; Griffiths, Kathleen M.; Bauer, Stephanie (International journal of environmental research and public health, 2022)
Eating disorder mental health literacy (ED-MHL) refers to knowledge about the symptoms, causes, and treatment of eating disorders (EDs) and is an important factor in people’s attitudes towards individuals with EDs and help-seeking for EDs. Associations between ED-MHL, stigma, ED symptomatology, and gender were investigated in a sample of N = 194 German high school students. Knowledge and myths about EDs were assessed with 18 factual statements about EDs and agreement/disagreement with common myths about ED. Students also completed the Universal Stigma Scale (USS), the Weight Concerns Scale (WCS), and demographic items. Students judged M = 8.39 (SD = 3.40) statements correctly, while the average agreement with all ED myths was low (M = 0.19, SD = 0.14). Greater ED-MHL was associated with lower stigmatization of EDs. Male participants were less knowledgeable and more likely to agree with the ED myths. Participants displayed moderate ED-MHL; however, certain aspects such as ED risk factors or symptoms of specific disorders such as anorexia nervosa and bulimia nervosa were less well known. These results can inform the design of future MHL interventions for adolescents.